Customer Relationship Management to Maximize Return on Marketing Investment : A Case Study in Pangripta Consulting - Nisa Nurrofiah; Cecep Safaatul Barkah; Tetty Herawati; Lina Auliana (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2023)
Economic conditions and a stabilizing business world present an opportunity for Pangripta Consulting, as many businesses need consulting services to help them adapt and face new challenges and competition. This study aims to identify strategies that companies can implement to optimize the return on their marketing investments. The study used a qualitative approach using primary data from interviews with Pangripta Consulting and secondary data from the company's historical data. The proposed strategy is based on the company's internal and external analysis using SWOT analysis. The results of this research are presented in the form of marketing strategies suggested through the implementation of customer relationship management programs.